2020
DOI: 10.1002/jwmg.21856
|View full text |Cite
|
Sign up to set email alerts
|

Wolverine Occupancy, Spatial Distribution, and Monitoring Design

Abstract: In the western United States, wolverines (Gulo gulo) typically occupy high‐elevation habitats. Because wolverine populations occur in vast, remote areas across multiple states, biologists have an imperfect understanding of this species' current distribution and population status. The historical extirpation of the wolverine, a subsequent period of recovery, and the lack of a coordinated monitoring program in the western United States to determine their current distribution further complicate understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Our model also suggested that asymptotic occupancy of wolverines in the Cascades is high, but short‐term use of any given area is low, consistent with estimates of moderate occurrence probability from previous studies conducted in the region (Lukacs et al. 2020). The difference in precision between continuous‐time and discrete‐time models is due to the need to discard >75% of detection events to create detection histories for the discrete‐time model (Guillera‐Arroita et al.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our model also suggested that asymptotic occupancy of wolverines in the Cascades is high, but short‐term use of any given area is low, consistent with estimates of moderate occurrence probability from previous studies conducted in the region (Lukacs et al. 2020). The difference in precision between continuous‐time and discrete‐time models is due to the need to discard >75% of detection events to create detection histories for the discrete‐time model (Guillera‐Arroita et al.…”
Section: Discussionsupporting
confidence: 89%
“…We found that this model improved inference relative to a discrete-time multi-scale occupancy model in our wolverine case study, decreasing standard deviation of estimated use probabilities by upwards of 50% (Table 1), and also provided more conservative use and instantaneous occupancy estimates. Our model also suggested that asymptotic occupancy of wolverines in the Cascades is high, but shortterm use of any given area is low, consistent with estimates of moderate occurrence probability from previous studies conducted in the region (Lukacs et al 2020). The difference in precision between continuous-time and discrete-time models is due to the need to discard >75% of detection events to create detection histories for the discrete-time model (Guillera-Arroita et al 2011).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations